On the rim of inspiration: performance of AWF tourism enterprises in Botswana and Rwanda. Issue 11 (2nd November 2017) - Black, Rosemary; Cobbinah, Patrick Brandful
ABSTRACT: Community-based natural resource management approaches including joint venture partnerships provide opportunities to achieve biodiversity conservation and associated tourism development. The African Wildlife Foundation (AWF) conservation enterprise model aims to improve the quality of life of communities and promote positive local attitudes towards conservation, and has been used to establish conservation lodges. To date, there has been no assessment of the performance of the conservation lodges in relation to this aim. This study used two case study AWF-initiated conservation lodges in Rwanda and Botswana to assess the performance of these conservation enterprises. The study adopted one-on-one structured questionnaire interviews with lodge staff and community residents. Analysis of economic and social performance and attitudes to conservation indicates that rural communities within the vicinity of the conservation lodges are generally benefitting from the existence of the lodges and associated tourism activity although to varying degrees, as well as promoting positive conservation attitudes among the community.